Representations of recent Peruvian history teaching and learning among prospective teachers in social sciences (Tempo e Argumento, 2021)
AbstractThis research focuses on the representations of recent Peruvian history teaching and learning among prospective teachers in social sciences. We ask two questions: how these representations of recent history teaching and learning are; and whether these representations might contribute to deal with the skill “build historical interpretations” provided for in the national curriculum. Within the grounded theory framework, we triangulate the information collected in a questionnaire, a narrative, and a semi-structured interview. Thus, we identified common representations and proposed 4 groups: narrators; identitarians; revealers; and analyticals. The conclusions show that prospective teachers feel insecure in addressing recent history topics because they see themselves as lacking the necessary strategies and disciplinary training. We notice the predominance of a representation of transmissive and organized teaching around rulers as protagonists. Only the ‘analyticals’ focus on teaching through topics that they link to current issues. The representations of learning among ‘narrators’ show that for them learning history is narrating facts objectively. The ‘identitarians’ and ‘revealers’ believe that learning recent history means recognizing the true interpretation of history characterized by bad government administration, corruption, injustice, and conflict between exploited and exploiters. Only the ‘analyticals’ propose activities related to skills to build historical thinking that might contribute to achieving the competence.Keywords: Initial teacher training; recent history; representations of teaching; representations of learning; history of Peru.